Establishment and application of a rapid new detection method for antimicrobial susceptibility testing of Klebsiella pneumoniae based on MALDI-TOF MS - Yapei Zhang; Fanghua Fan; Xuan Wang; Jie Zhu; Shilei Dong (Microbiology Spectrum)
ABSTRACT The earlier appropriate treatment of Klebsiella pneumoniae infections according to the antimicrobial susceptibility profile based on the minimum inhibitory concentration (MIC) has a great clinical benefit. Our objective was to establish a matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS)-based antimicrobial susceptibility test (AST) for K. pneumoniae that produces reliable results within a few hours. Our rapid method is similar to the classical turbidity-based microdilution method. We confirmed, theoretically and experimentally, that MALDI-TOF MS can replace the naked eye in judging the results (MICMS) by “seeing” the bacterial growth in the presence of different concentrations of antibiotics, including determination of the lower limit of bacterial count detection (4 × 105 cfu), the optimal period of incubation (2 h), and bacterial growth curve assay. Based on the study mentioned above, we determined the susceptibility of K. pneumoniae to imipenem. The MICMS and MIC data agreed over 85% (40/46) within 1 dilution range. Susceptibility profiles determined with our rapid method and the reference broth microdilution method were also compared. MICMS resulted in 97.9% (45/46) category agreement, 2.2% minor discrepancies, no major discrepancies, and no very major discrepancies. The summarized category agreement resulted in a kappa coefficient of almost 1 for weighted Cohen’s kappa, which could be considered a nearly perfect agreement. It took just 2 h to produce a susceptibility profile with a low failure rate using our new rapid AST method, a work day earlier than the broth microdilution method.IMPORTANCEEmpirical antimicrobial use before antimicrobial susceptibility test (AST) is necessary but risks patient harm and excess costs. It is particularly worrying that the inappropriate use of carbapenems has allowed carbapenem-resistant Klebsiella pneumoniae to become the commonest transmissible carbapenem-resistant Enterobacterales worldwide. Guidelines recommend targeted therapy based on minimum inhibitory concentration results, which directly reflect the effectiveness of antibacterial drugs. The gold standard method of AST relies on visible bacterial growth, causing long turnaround times. Current rapid AST techniques are hampered by factors such as high costs, technological complexities, and limited detection capabilities. We present a novel rapid method and applied to the determination of the susceptibility of K. pneumoniae to imipenem. It took just 2 h to produce a susceptibility profile with a low failure rate, a work day earlier than the standard method. Our method is potentially a faster, more precise, cost-efficient, and user-friendly AST method that can enhance the effectiveness of treatment strategies.